The effects of breed and genomic inbreeding on milk, fat and protein lactation yields and fertility traits in pasture-based dairy cows in Argentina - Beribe MJB; Carignano HA; Poli MA; Lopez-Villalobos N (Cambridge University Press, 2024)
The objective of the current study was to evaluate the effects of breed and genomic inbreeding on 305-day lactation yields of milk, fat and protein; and fertility traits of pasturebased dairy cows in Argentina. The genomic inbreeding and heterozygosity of 890 firstlactation cows and 27 bulls were calculated through methods based on the genomic relationship matrix and run of homozygosity using 44 174 SNPs. Cows were classified into 4 breed groups: Holstein, Holstein crossbred, Holstein-Jersey crossbred, and Jersey crossbred. The effect of genomic inbreeding was not significant on production traits, but inbred cows increased 3.0 days calving to conception interval per 1% genomic inbreeding. On average, purebred Holstein cows produced 1119 kg milk, 22 kg fat, and 30 kg protein more than Jersey crossbred cows. In the case of the fertility traits, Jersey crossbred cows had 45 days shorter calving to conception interval than purebred Holstein cows. A possible reason for the non-significant effects of genomic inbreeding of production and fertility traits is that these effects were evaluated in a crossbred population in which levels of heterozygosity would operate to some extent in the opposite direction to levels of genomic inbreeding.
Keywords: calving to conception interval; cattle breed; genomic inbreeding values; milk production; run of homozygosity